Impact of puberty, sex determinants and chronic inflammation on cardiovascular risk in young people - Allalou, Amal; Peng, Junjie; Robinson, George A.; Marruganti, Crystal; D’Aiuto, Francesco; Butler, Gary; Jury, Elizabeth C.; Ciurtin, Coziana (Frontiers in Cardiovascular Medicine, 2023)
Worrying trends of increased cardiovascular disease (CVD) risk in children, adolescents and young people in the recent decades have channelled research and public health strategies to tackle this growing epidemic. However, there are still controversies related to the dynamic of the impact of sex, age and puberty on this risk and on cardiovascular health outcomes later in life. In this comprehensive review of current literature, we examine the relationship between puberty, sex determinants and various traditional CVD-risk factors, as well as subclinical atherosclerosis in young people in general population. In addition, we evaluate the role of chronic inflammation, sex hormone therapy and health-risk behaviours on augmenting traditional CVD-risk factors and health outcomes, ultimately aiming to determine whether tailored management strategies for this age group are justified.